Fabrication of Pascal‐triangle Lattice of Proteins by Inducing Ligand Strategy. Issue 24 (1st April 2020) - Liu, Rongying; Kochovski, Zdravko; Li, Long; Yin, Yue‐wen; Yang, Jing; Yang, Guang; Tao, Guoqing; Xu, Anqiu; Zhang, Ensong; Ding, Hong‐ming; Lu, Yan; Chen, Guosong; et al.
Abstract: A protein Pascal triangle has been constructed as new type of supramolecular architecture by using the inducing ligand strategy that we previously developed for protein assemblies. Although mathematical studies on this famous geometry have a long history, no work on such Pascal triangles fabricated from native proteins has been reported so far due to their structural complexity. In this work, by carefully tuning the specific interactions between the native protein building block WGA and the inducing ligand R‐SL, a 2D Pascal‐triangle lattice with three types of triangular voids has been assembled. Moreover, a 3D crystal structure was obtained based on the 2D Pascal triangles. The distinctive carbohydrate binding sites of WGA and the intralayer as well as interlayer dimerization of RhB was the key to facilitate nanofabrication in solution. This strategy may be applied to prepare and explore various sophisticated assemblies based on native proteins. Abstract : A Pascal‐triangle lattice is constructed by using a careful selection of protein building blocks with anisotropic shapes and two sets of carbohydrate binding sites. Moreover, the dynamic and exchangeable nature of non‐covalent interactions makes the further manipulation of 2D lattices to 3D crystals possible.